أثر استراتيجيات المركز التنافسي في اتجاهات الأطباء نحو تميز الأدوية الجنيسة دراسة ميدانية على عينة من أطباء ولاية باتنة–الجزائر - لحول سامية (جامعة الوادي University Of Eloued, 2024)
تهدف هذه الدراسة إلى تحديد أثر استراتيجيات المركز التنافسي المستخدمة من طرف المؤسسات الدوائية في اتجاهات قادة الرأي الصحي الممثلين في الأطباء نحو تميز الأدوية الجنيسة في الجزائر. وخلصت الدراسة إلى وجود أثر ذو دلالة إحصائية لاستراتيجيات المركز التنافسي على الأطباء نحو تميز الأدوية الجنيسة في الجزائر. وأن هناك اتجاه ايجابي من قبل الأطباء نحو الأدوية الجنيسة في الجزائر. كما أظهرت نتائج الدراسة أيضا أن استراتيجيات المركز التنافسي التي تتبعها هذه المؤسسات تختلف من حيث أهميتها في تشكيل اتجاهات الأطباء نحو تميز الأدوية الجنيسة. This study aims to determine the impact of positioning strategies used by pharmacological institutions on the attitudes of health opinion leaders represented in doctors towards the Excellence of generic drugs in Algeria. The study concluded that there is a statistically significant effect of the strategies of the positioning on doctors towards Excellence generic drugs in Algeria. And that there is a positive trend by doctors towards generic drugs in Algeria. The results of the study also showed that the positioning strategies pursued by these institutions differ in terms of their importance in shaping doctors ’attitudes towards the Excellence of generic drugs.
the impact of positioning strategies on the attitudes of health opinion leaders towards the Excellence of generic drugs Empirical study on a sample of doctors in the state of Batna - Algeria
Keywords: المركز التنافسي; التميز; قادة الرأي الصحي; الأدوية الجنيسة; الجزائر; positioning; Excellence; Health Opinion Leaders; Algeria; Generic Medicines